Frequency of Diabetic Nephropathy among Patients of Type 2 Diabetes Mellitus: Diabetic Nephropathy among Type 2 Diabetes Mellitus - Jamil, Muhammad Irfan; Hussain, Yasir; Khan, Muhammad Shahid Nawaz; Shahzad, Anjum; Iqbal, Azhar; Ahmed, Adeel; Naeem, Iqra (Pakistan Journal of Health Sciences, 2025)
Diabetic Nephropathy (DN) is a predominant consequence of Type 2 Diabetes Mellitus (T2DM), contributing to chronic renal disease. Objective: To determine the frequency of diabetic nephropathy and its correlation with glycemic control. Methods: A cross-sectional study was conducted at the Nephrology and Diabetic OPD of Lahore General Hospital from July to November 2024. A total of 282 type 2 diabetic patients were enrolled. Clinical evaluation, fundoscopy, neurological examination, and laboratory tests were performed. Diabetic nephropathy was diagnosed based on albuminuria and eGFR. Statistical significance was set at p < 0.05. Results: Out of 282 patients, 150 (53.2%) were males and 132 (46.8%) females. The majority (43.3%) were aged 50–59 years. Microalbuminuria and macroalbuminuria were present in 20.9% and 32.3%, respectively. Mean serum creatinine and eGFR were 1.16 ± 0.53 mg/dL and 68.15 ± 24.58 mL/min/1.73m². Mean HbA1c and FBS levels were 8.40 ± 1.84% and 137.03 ± 19.19 mg/dL. Hypertension was noted in 41.5%. Diabetic nephropathy was significantly more prevalent in those with FBS >140 mg/dL (29.1%) and HbA1c >7.5% (32.6%) compared to those with lower values (p < 0.05). Declining eGFR was also significantly associated with nephropathy, with most cases found in those with eGFR <60 mL/min/1.73m² (p < 0.001). Conclusion: The study revealed a high frequency of diabetic nephropathy in type 2 diabetes, linked to poor glycemic control, declining eGFR and complications.